Explaining Satisfaction at a Foreign Tourism Destination – an Intra-Generational Approach. Evidence within Generation Y from South Africa and Romania - Norbert Haydam; Theodor Purcarea; Tudor Edu; Iliuta Costel Negricea (Amfiteatru Economic Journal, 2017)
Generation Y poses interesting consumption behaviour peculiarities comparing to the other generational groups. This paper focuses on two age layers of Generation Y, 20-24 years old and 25-29 years old, with the purpose of modelling satisfaction at a foreign tourism destination based on destination attributes and demographic variables. A mixed qualitative - quantitative research design was employed using equal samples of 30 and, subsequently, of 800 individuals from Romania and South Africa. Based on a comprehensive literature review on satisfaction and its constructs and on Generation Y, a model for explaining satisfaction was built and tested in Romania and South Africa on the two designated age layers using logistic regression. The findings show similarities and differences between the two countries enriching the literature on generational constituents and offering practical insights to tourism businesses. Finally, the model proposed and tested in this paper can be easily replicated in other parts of the world.
Keywords: D12; M31; Z32; 330; Generation Y; satisfaction; tourism; logistic regression; Romania; South Africa